Effect of active modified atmosphere and cold storage on the postharvest quality of cherry tomatoes - Fagundes, Cristiane; Moraes, K.; Pérez-Gago, María B.; Palou, Lluís; Maraschin, M.; Monteiro, A. R. (2017)
The effects of active modified atmosphere packaging (MAP) on the postharvest quality of cherry tomatoes stored at cold temperature (5 degrees C) and in bi-oriented polypropylene/low density polyethylene BOPP/LDPE bags were investigated. The atmosphere composition used in the packaging was 5% O-2 + 5% CO2 (MAP), and synthetic air (control). The variables measured were weight loss, firmness, sugar, organic acids, color, lycopene, respiration rate, and ethylene biosynthesis over 25 days. The results showed that active MAP could extend the shelf life of cherry tomatoes to 25 days and the gas concentration could influence the postharvest quality of cherry tomatoes. MAP treatment decreased the respiration rate and ethylene production rate while reducing weight loss, lycopene biosynthesis, and the formation of red color. Through the use of MAP it was possible to maintain firmness and delay changes in sugar and organic acid contents. The combination of active MAP and low temperature treatments was effective with regard to delaying maturity during the storage period, and preserving the quality of cherry tomatoes. (C) 2015 Elsevier B.V. All rights reserved.